2009
DOI: 10.1063/1.3077942
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Couette–Taylor flow device with active minimization of secondary circulation

Abstract: A novel Taylor-Couette experiment has been developed to produce rotating shear flows for the study of hydrodynamic and magnetohydrodynamic instabilities which are believed to drive angular momentum transport in astrophysical accretion disks. High speed, concentric, corotating cylinders generate the flow where the height of the cylinders is twice the radial gap width. Ekman pumping is controlled and minimized by splitting the vertical boundaries into pairs of nested, differentially rotating rings. The end rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(90 citation statements)
references
References 18 publications
3
86
1
Order By: Relevance
“…Schartman et al (2012) state that these incompatible results are caused by differing interpretations of finite-size effects, namely Ekman circulation produced by the axial boundaries. In the Princeton experiments (Ji et al 2006;Schartman et al 2009;Burin et al 2010;Schartman et al 2012) the aspect ratio is small (Γ ≈ 2) and therefore finite-size effects would likely dominate. To minimize Ekman circulation, their axial boundaries are split into pairs of rings that can independently rotate with respect to the cylinders.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Schartman et al (2012) state that these incompatible results are caused by differing interpretations of finite-size effects, namely Ekman circulation produced by the axial boundaries. In the Princeton experiments (Ji et al 2006;Schartman et al 2009;Burin et al 2010;Schartman et al 2012) the aspect ratio is small (Γ ≈ 2) and therefore finite-size effects would likely dominate. To minimize Ekman circulation, their axial boundaries are split into pairs of rings that can independently rotate with respect to the cylinders.…”
Section: Discussionmentioning
confidence: 99%
“…To further address this issue from a numerical standpoint, Avila (2012) performed direct numerical simulations of our experimental geometry as well as the Princeton apparatus (Ji et al 2006;Schartman et al 2009;Burin et al 2010;Schartman et al 2012). Avila found that the axial boundaries drive secondary flows that enhance the global angular momentum transport.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations